The December Revolt Statement (Description) in Kazakh Literature - Saltanat Amanzhol, Nassikhat Mursalimova, Gulzhakhan Orda, Nurbol Khudaibergenov, Zhansulu Sarsenbayeva, (Opción, 2019)
The object under the study of this article is the December revoltdescription that outlined in Kazakh literature. Original artworks in thegenre of poems, proses, and dramas are served in detail and thoroughly  studied by the comparative-historical method. As a result, the victims of wrong politics of a stud ram for sacrifice should have constant care and attention of the state. In conclusion, the living truth is that Kazakh people gained the independence by thousands of Kazakh youths’ blood.